Effect of non-electrical parameters in fabrication of micro rod using BEDG. Issue 11 (18th August 2019) - Kar, Siddhartha; Patowari, Promod Kumar
ABSTRACT: This paper presents an experimental study of fabrication of micro rods by block electrical discharge grinding (BEDG) process, with the aid of an assisting block electrode. The effect of non-electrical parameters such as feed rate (FR) and tool rotation speed (TRS) is investigated, by considering brass rod of 1.8 mm diameter as workpiece and rectangular block of brass as tool material. Machining time (MT), average diameter (AD), and standard deviation in diameter (SDD) of rod are the evaluated response measures. The process parameters are optimized for lower MT, AD, and SDD. Further, overall evaluation criteria (OEC) have been formulated for simultaneous optimization of all the response measures. From analysis of variance (ANOVA), it is ascertained that FR significantly influences MT, whereas TRS significantly influences both AD and SDD. The topography of the micro rods has been characterized by optical microscopy and scanning electron microscopy (SEM) analysis. With optimum parameters of OEC ( F R = 2.5 μ m, T R S = 1250 r p m ), a micro rod with AD of 156.86 µm and SDD of 7.54 µm is fabricated successfully, which suggests that fairly linear micro rod can be fabricated by optimizing the non-electrical parameters in BEDG process.